2023
DOI: 10.1007/s12257-022-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Enhance the Biosynthesis of Monounsaturated Fatty Acids in Escherichia coli

Abstract: Fueled by a variety of industrial applications ranging from bioplastics to cosmetics and pharmaceuticals, the global demand for unsaturated fatty acids is steadily rising. Most of these applications build on monounsaturated fatty acids with a chain length of 16 or 18 carbon atoms, rendering these compounds valuable industrial assets. While of high industrial interest, monounsaturated fatty acids with a chain length of 8 to 12 carbon atoms are hard to produce using conventional chemical or plant-based productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 175 publications
0
1
0
Order By: Relevance
“…MD simulations and experiments of GlpG revealed that careful investigations on the protein packing and dynamics could improve the enzyme stability. Rational engineering of proteins based on structural analysis has been widely attempted to improve protein stability [ 29 , 30 , 31 , 32 ] and discovery and engineering of stable or active enzymes are very crucial for biological production of value-added chemicals [ 33 , 34 , 35 , 36 , 37 ]. Thus, the results obtained in this study can be applied to protein stabilization in various environments.…”
Section: Resultsmentioning
confidence: 99%
“…MD simulations and experiments of GlpG revealed that careful investigations on the protein packing and dynamics could improve the enzyme stability. Rational engineering of proteins based on structural analysis has been widely attempted to improve protein stability [ 29 , 30 , 31 , 32 ] and discovery and engineering of stable or active enzymes are very crucial for biological production of value-added chemicals [ 33 , 34 , 35 , 36 , 37 ]. Thus, the results obtained in this study can be applied to protein stabilization in various environments.…”
Section: Resultsmentioning
confidence: 99%